Preliminary behaviour observations of the Javan rhinoceros (Rhinoceros sondaicus) based on video trap surveys in Ujung Kulon National Park - Hariyadi, Adhi; Setiawan, Ridwan; Daryan, Amir; Yayus, Asep; Purnama, Hendra (Pachyderm, 2010)
The behaviours of ten critically endangered Javan rhinoceros (Rhinoceros sondaicus) were observed using video camera traps on the peninsula of Ujung Kulon National Park (06 o 38’30’–06 o 52’30’ south and 105 o 12’00’–105 o 37’30’ east), and were organized as descriptive lists of activities (ethogram). Behavioural data were analyzed by examining the length of time each individual rhino displayed a specific activity (duration). Duration of each activity was calculated as a proportion within a total observation time (length of rhino observation in video recording). In addition to duration, the frequency of each activity was recorded. A quantitative analysis summarizing duration and frequency of activities will be used as baseline information about Javan rhino behaviours that can enrich our knowledge of this reclusive species. The results from this study suggest that the use of video trap equipment for quantifying the behaviour of Javan rhinoceros is promising. On a observé les comportements de dix rhinocéros de Java (Rhinoceros sondaicus), espèce gravement menacée, en utilisant des pièges d’appareil vidéo sur la péninsule du Parc National d’Ujung Kulon (06o 38’30’-06o 52’30’ sud et 105o 12’00’-105o 37’30’ est) et on a les répertoriés en listes descriptives d’activités (éthogramme). On a analysé les données behavioristes en examinant la durée dans laquelle chaque rhinocéros individuel affichait une activité spécifique (durée). On a calculé la durée de chaque activité comme une proportion du temps total d’observation (longueur d’observation du rhinocéros dans l’enregistrement vidéo). En plus de la durée, on a enregistré la fréquence de chaque activité. Une analyse quantitative qui résume la durée et la fréquence des activités sera utilisée comme informations de référence sur le comportement du rhinocéros de Java qui peuvent enrichir nos connaissances de cette espèce recluse. Les résultats de cette étude suggèrent que l’utilisation de matériel de piège vidéo pour mesurer le comportement du rhinocéros de Java est prometteuse.